Evaluación de la gestión de prevención de riesgos laborales y su incidencia en el desempeño de los transportistas de la compañía CONTRANSPESA S.A. del cantón El Empalme provincia del Guayas año 2014 - Giraldo Chacón, Bolívar Antonio (2015)
EVALUATION OF THE MANAGEMENT AND PREVENTION OF OCCUPATIONAL HAZARDS AND THEIR IMPACT ON THE PRFOMANCE OF THE BARRIERS COMPANY OF CONTRASPESA S.A. Del Canton El Empalme provincial del Guayas, Year 2014.This is directed to minimize the risk on labour and establish the impact they have on the Company, presented by events in past years in this Company because of the misuse of the working tools and methods. The methods used in this research was an analytical method, which served to get to know the strengths and weaknesses of CONTRASPESA S.A. We also applied the deductive method for the analysis of labour risk, that existed in within the company, the descriptive method allowed us to get to know situations, process and people involved in the transportation market, through the synthetic method a general analysis of the procedures applied in the company.The inductive method was used to link and generalize the result of the surveys and interviews. Finally the quantities method helped us to the collection, study and analysis of the result that will allow solidly substantive or disprove the hypothesis raised. After all these research methods were put in place, we reach the conclusion, that even that the company has all the protective equipment, still not been given proper use, since the in the Company there ben minor accidents, all down to not applying the correct procedures given by Company policy and internal rules. In many occasions the staff do not use at all the correct equipment to using adequate protection. Trough an analysis F.O.D.A, many weaknesses were detected, the lack of monitoring of the heads of departments leads to drivers to not use the tool, equipment or correct procedures properly.